Optimal placement of different types of distributed generation sources in distribution networks using differential evolution - Muhammad Helmi Solihin bin Basirun (2023)
Distributed generation was already been known on this century as a small scale of generation that being distribute close to customer. In other word, this kind generation located at distribution side. In this thesis, the application of the distributed generation will be obsedrved to determine how it responses in different location and what is the suitable size to be installed.